2013
DOI: 10.29313/mimbar.v29i2.394
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh dari Nilai-Nilai Islam terhadap Kinerja Kerja

Abstract: Abstract. The purpose of this research is to study about the influence of Islamic value and Islamic work ethics to the work performance of employee of small enterprises in Bandung City. This research was the deductive quantitative. The samples were 350 employees that determined by proportional way. Using SEM, Estimation sshows that the Islamic value did not direcly influence on work performance. The Islamic value influences on work performance through Islamic work ethics. This mean that in order to improve job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…ASKES (PERSERO) Manado branch states that salaries significantly affect employee performance (Darendehe, 2013). H3: Salary has a positive and significant effect on employee performance Other research conducted by Amaliah suggests that IWE (Islamic Work Ethic) has a significant effect on employee performance (Amaliah, 2013). Besides, in other research literature conducted by Rusyanti on Hotel employees in Solo, it is concluded that Islamic Work Ethics affect employee performance (Rusyanti, 2019) Research conducted by Susanto suggests that work motivation has influenced employee performance, job satisfaction has influenced employee performance, and work discipline influences employee performance (Susanto, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…ASKES (PERSERO) Manado branch states that salaries significantly affect employee performance (Darendehe, 2013). H3: Salary has a positive and significant effect on employee performance Other research conducted by Amaliah suggests that IWE (Islamic Work Ethic) has a significant effect on employee performance (Amaliah, 2013). Besides, in other research literature conducted by Rusyanti on Hotel employees in Solo, it is concluded that Islamic Work Ethics affect employee performance (Rusyanti, 2019) Research conducted by Susanto suggests that work motivation has influenced employee performance, job satisfaction has influenced employee performance, and work discipline influences employee performance (Susanto, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Prinsip tauhid dalam implementasinya di dalam muamalah sangatlah luas. Dalam konteks individu, prinsip ini juga dinamakan dengan prinsip ketuhanan di mana nilai-nilai agama menjadi pemandu dalam aktifitas bekerja [25], termasuk juga dalam eksploitasi hasil laut seperti sikap bersyukur, optimis (tawakkal), dan sungguh-sungguh dalam bekerja.…”
Section: Berpegang Teguh Pada Prinsip Tauhidunclassified
“…Islamic work ethics gives meaning to the work we do, that work in the world is one of the determinants of happiness in the hereafter. With these beliefs and awareness, a person's motivation will be greater for doing work even without any incentives (Amaliah et al, 2013). Some jobs will get different treatment depending on how a person sees and believes in his work.…”
Section: Function and Purpose Of Islamic Work Ethicsmentioning
confidence: 99%